Hubungan Pengetahuan Tentang Vulvae Hygiene Selama Menstruasi dengan Kejadian Pruritus Vulvae Pada Siswi: Vulva hygiene - Manoppo, Ivanna; Turangan, Fiolanda Deasintha Bella (NUTRIX, 2024)
Abstract Pruritus vulvae is a common complaint experienced by adolescents related to reproductive health, characterized by itching in the genital area during menstruation. This occurs because, during menstruation, the vulva becomes moist, and both blood and sweat are secreted and stick to the vulva. If adolescents do not properly maintain hygiene in the vulva area during this time, fungi and bacteria will thrive, leading to itching in the vulva. This study aims to determine the relationship between the level of knowledge about vulvar hygiene and the incidence of pruritus vulvae among students at SMPN 4 Ratahan. The research method used was descriptive correlation with a cross-sectional approach. Statistical tests included frequency, percentage, and Spearman's correlation. The sampling technique used was purposive sampling. The results, from a total of 45 respondents, showed that the majority had a low level of knowledge, with 32 respondents (71.1%), followed by sufficient knowledge in 9 respondents (20.0%), and good knowledge in 4 respondents (8.9%). As for the incidence of pruritus vulvae, 25 respondents (55.6%) experienced moderate pruritus, 13 respondents (28.9%) experienced severe pruritus, and 7 respondents (15.6%) experienced mild pruritus. There is a relationship between vulvar hygiene knowledge and the incidence of pruritus vulvae, with a P-value of 0.000 and an r-value of -0.658. The recommendation for future researchers is to investigate the factors influencing the incidence of pruritus vulvae among adolescents using an in-depth interview technique. Keywords: Adolescents, Knowledge, Pruritus Vulvae, , Vulvae Hygiene Abstrak Pruritus vulva merupakan keluhan yang sering dialami oleh remaja terkait dengan kesehatan reproduksi berupa gatal-gatal pada daerah kemaluan saat menstruasi. Hal ini disebabkan pada saat menstruasi vulva menjadi lembab, kemudian saat menstruasi darah dan keringat keluar serta menempel pada vulva. Jika pada saat itu remaja tidak menjaga perilaku kebersihan pada area vulva dengan benar maka jamur dan bakteri akan tumbuh subur sehingga menyebabkan rasa gatal pada vulva. Penelitian ini bertujuan untuk mengetahui hubungan tingkat pengetahuan vulva hygiene dengan kejadian pruritus vulva pada siswi di SMPN 4 Ratahan. Metode yang digunakan deskriptif korelasi dengan pendekatan cross sectional. Uji statisktik menggunakan frekuensi, presentase dan spearman correlatioan. Teknik sampling yang digunakan yaitu purposive sampling. Hasil penelitian ini dengan jumlah 45 responden didapati tingkat pengetahuan yang paling banyak yaitu pengetahuan kurang 32 responden (71,1%), pengetahuan cukup 9 responden (20,0% ), dan pengetahuan baik 4 responden (8,9%). Hasil dari kejadian pruritus vulva didapati siswi yang mengalami pruritus vulva sedang berjumlah 25 responden (55,6%), pruritus vulva berat berjumlah 13 responden (28,9%) dan pruritus vulva ringan berjumlah 7 responden (15,6%). Ada hubungan antara Pengetahuan Vulva Hygiene dengan kejadian Pruritus Vulva dengan P= 0,000 dan r= - 0,658. Rekomendasi bagi peneliti selanjutnya untuk melihat faktor-faktor yang mempengaruhi kejadian pruritus vulva pada remaja dengan teknik penelitian indepth interview. Kata Kunci : Pengetahuan, Pruritus Vulva, Remaja, Vulvae Hygiene